2010
DOI: 10.1590/s0103-64402010000200009
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic analysis of root canal fillings: influence of two sealers on the perception of voids

Abstract: The aim of this ex vivo was to investigate if two radiopaque root canal sealers with different formulations would influence the radiographic perception of root canal fillings. The root canals of 48 extracted maxillary canines were prepared and randomly assigned to 3 groups of 16 specimens each. In each group, the root canals were filled by lateral condensation of gutta-percha and one of the tested sealers: Endométhasone, Sealer 26, or a non-radiopaque sealer. A through-and-through void was simulated in half of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…In addition, assessments of the voids within the restoration are facilitated when material experiences adequate radiopacity 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, assessments of the voids within the restoration are facilitated when material experiences adequate radiopacity 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Presence of voids in the obturation is one predicament which might provide pathways for leakage and the possibility of microorganism and toxin retention, leading to post-treatment failures. [15][16][17] Factors that influence the location and size of the voids include the type, viscosity, and consistency of the paste, the method used to apply the paste, and operator skill and experiences. [4,18] The results of the present study showed that in Group I where the root canals were filled using lentulospiral, presence of voids was frequently observed [Figure 1].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the patterns of sealer distribution through the root canal may depend not only on the physical properties of the sealer, but also on the filling technique applied 8,23 . In this sense, physical properties other than radiopacity seemed to influence, in a different way, the radiographic perception of defective or adequate root canal fillings performed with lateral condensation 6 . Given that only two commercial root canal sealers were tested in this study, the adoption of other sealers with different physical characteristics could generate stronger evidence about the unique influence of radiopacity on the radiographic detection of root canal filling defects.…”
Section: Discussionmentioning
confidence: 99%